Upaya Mahasiswa KKM Dalam Memupuk Nasionalisme di Pedesaan Pada Peringatan Hari Kemerdekaan Republik Indonesia - Sunardi Sunardi; Mochammad Darip; Basuki Rakhim Setya Permana; Gelard Untirtha Pratama; Ali Rohman (Batara Wisnu : Indonesian Journal of Community Services, 2024)
The lack of nationalistic activities on Independence Day is often a major obstacle in building a sense of love for the homeland among rural communities. Remote geographical conditions, inadequate infrastructure, and uneven levels of education make this challenge even more real. One example that shows a decline in the spirit of nationalism in welcoming the commemoration of Independence Day is the community living in Cirumpak Village, Kronjo District. This is indicated by the lack of preparation of the community in welcoming Independence Day compared to urban communities. Bina Bangsa University through a community service program in the form of Student Work Lectures consisting of students and lecturers initiated to re-cultivate the spirit of nationalism for the community living in the village with one approach strategy, namely through organizing activities that are educational, participatory, and entertaining, but still have a strong national content value with the aim of increasing the sense of love for the homeland among rural communities. Starting from the planning stage, implementation of activities, to evaluation which shows that this activity was successfully implemented in accordance with the expected targets and objectives. As many as 78.33% of the 30 respondents stated that they were satisfied or happy with the activity, while around 64.44% of respondents indicated that this activity had a positive impact in increasing the spirit of nationalism